Adhesive wear behaviour of surface modified bamboo filler reinforced polymer composite under different contact condition. Issue 15 (23rd November 2022) - Paul, Rajdeep; Bhowmik, Sumit
ABSTRACT: An experimental study has been conducted to evaluate the adhesive wear behavior of bamboo filler-reinforced polymer composite. Bamboo has the significant attention of investigators due to its benefits over human-made fibers. The bamboo fillers' surface is treated by the alkali treatment process and the composite is prepared with a variation of micro bamboo particle support (i.e. 0, 2.5, 5, 7.5, 10, and 12.5%). The study of tribological characterization is explored for dry, wet, and heated sliding contact state using the pin-on-disk tribomachine counter to a stainless steel disc. Modified bamboo filler composite exhibited better interaction between filler and matrix, which improve the wear resistance capacity of the composite. From the experimental result it is found that specific wear rate and coefficient of friction is lesser in wet condition compared to dry and heated state conditions. Moreover, lower filler content offered enhanced wear performance related to the higher filler content composite. In case of dry sliding contact, debonding and plastic deformation are witnessed on the composite surfaces. However, the worn regions are minimal under wet state condition. Further, in case of the heated state, a thin layer created on the exterior of composite which safeguards the surface from further worn.